Improved cloud radio access network based fair network model in internet pricing - Indrawati Indrawati; Fitri Maya Puspita; Desta Wahyuni; Evi Yuliza; Oki Dwipurwani (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In this study, the pricing scheme that will be formed is a model from the previous research model involving model of cloud-radio access network (C-RAN) and fair network management models. This model combines the benefits of internet service provider (ISP) and service quality (QoS) obtained by internet users, one of which is fair network factors. The model used is a nonlinear equation and is solved by the LINGO 13.0 program to get the optimal solution. The results show that the pricing scheme with regard to service quality generates maximum revenue for ISPs. Based on the improved C-RAN model that are classified into 2 cases, the optimal results in the improved model, the optimal value is found in the pricing scheme in case 1 of by conducting numerical computation using  hotspot traffic from local server.